2012
DOI: 10.1371/journal.pone.0033316
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 DNA CpG Dinucleotide Methylation and Epigenetic Regulation of Viral Expression

Abstract: CpG DNA methylation is one of the main epigenetic modifications playing a role in the control of gene expression. For DNA viruses whose genome has the ability to integrate in the host genome or to maintain as a latent episome, a correlation has been found between the extent of DNA methylation and viral quiescence. No information is available for Parvovirus B19, a human pathogenic virus, which is capable of both lytic and persistent infections. Within Parvovirus B19 genome, the inverted terminal regions display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…A further level of regulation of viral expression can be at the epigenetic level [107]. In this respect, CpG DNA methylation is one of the main epigenetic modifications playing a role in the control of gene expression.…”
Section: Expression Profilementioning
confidence: 99%
See 2 more Smart Citations
“…A further level of regulation of viral expression can be at the epigenetic level [107]. In this respect, CpG DNA methylation is one of the main epigenetic modifications playing a role in the control of gene expression.…”
Section: Expression Profilementioning
confidence: 99%
“…For example, in the semipermissive UT7 cells, after a few rounds of productive replication the virus can still be detected for extended periods of time showing a progressive loss of activity [55,107], and also in nonpermissive systems such as U937 cells the viral DNA can be maintained within cells for some time in the absence of detectable viral activity [107]. These systems may mirror what happens in vivo.…”
Section: Virus Persistence Following In Vitro Infections Carrier Cumentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, Bonvicini et al demonstrated for the first time CpG methylation of a single-stranded DNA (ssDNA) virus (18). They showed extensive CpG methylation of parvovirus B19 both in clinical samples and in cell culture models (18). Studies demonstrating the loss of CpG dinucleotides in small DNA viruses (Ͻ30 kb) have focused only on viruses infecting humans or higher-order mammals.…”
mentioning
confidence: 99%
“…To test this hypothesis, we chose to investigate the CpG dinucleotide content of parvoviruses, which are single-stranded DNA viruses infecting a wide range of hosts, spanning from insects to primates, including humans. We believe that parvoviruses are an appropriate choice to test our hypothesis for the following reasons: (i) parvoviruses do not encode their own polymerase and their replication is dependent on the cellular replication machinery (19,20), (ii) parvoviruses are known for their rapid adaption to the host (21), (iii) recent studies on parvovirus B19 confirm that parvovirus DNA is extensively methylated in humans (18), (iv) single-stranded methylated DNA is more rapidly deaminated than double-stranded methylated DNA (22), and (v) parvoviruses spanning across different subfamilies share common ancestral origins (23). Therefore, we believe that parvoviruses are suitable to study host-driven evolution of viruses.…”
mentioning
confidence: 99%